How Can Music Influence the Autonomic Nervous System Response in Patients with Severe Disorder of Consciousness? - Riganello, Francesco; Cortese, Maria D.; Arcuri, Francesco; Quintieri, Maria; Dolce, Giuliano (Frontiers in Neuroscience, 2015)
Activations to pleasant and unpleasant musical stimuli were observed within an extensive neuronal network and different brain structures, as well as in the processing of the syntactic and semantic aspects of the music. Previous studies evidenced a correlation between autonomic activity and emotion evoked by music listening in patients with Disorders of Consciousness (DoC). In this study, we analyzed retrospectively the autonomic response to musical stimuli by mean of normalized units of Low Frequency (nuLF) and Sample Entropy (SampEn) of Heart Rate Variability (HRV) parameters, and their possible correlation to the different complexity of four musical samples (i.e. Mussorgsky, Tchaikovsky, Grieg and Boccherini) in Healthy subjects and Vegetative State/Unresponsive Wakefulness Syndrome (VS/UWS) patients. The complexity of musical sample was based on Formal Complexity and General Dynamics parameters defined by Imberty’s semiology studies. The results showed a significant difference between the two groups for SampEn during the listening of Mussorgsky’s music and for nuLF during the listening of Boccherini and Mussorgsky’s music. Moreover, the VS/UWS group showed a reduction of nuLF as well as SampEn comparing music of increasing Formal Complexity and General Dynamics. These results put in evidence how the internal structure of the music can change the autonomic response in patients with DoC. Further investigations are required to better comprehend how musical stimulation can modify the autonomic response in DoC patients, in order to administer the stimuli in a more effective way.